Optimization of Carrier-Based Dry Powder Inhaler Performance: A Review - Tanu Mehta; Saeed Najafian; Komalkumar Patel; Justin Lacombe; Bodhisattwa Chaudhuri (Pharmaceutics)
Dry powder inhalers (DPI’s) are becoming increasingly popular due to growing interest in pulmonary drug delivery and their performance is the net result of a series of processes carried out during the formulation development and manufacturing process such as excipient selection, blending, milling, filling, and spray drying. To reach the small airways of the deep lung, the active pharmaceutical ingredients (API) particles need to have an aerodynamic diameter of 1–5 μm to avoid impaction and particle sedimentation in the upper respiratory tract, and due to this small particle size, the powder becomes highly cohesive resulting in poor flow. Therefore, API is usually blended with a coarse carrier to improve flowability, and due to its large size, it is more fluidizable than the micronized drug. Carrier-based DPI formulations usually consist of micronized drugs, a coarse carrier, and additional components, such as micronized lactose and force control agents, including magnesium stearate or leucine. Additionally, the manufacturing process of DPIs relies heavily on powder processing technologies, such as the micronization of API, blending, and powder filling. The aerosol performance of a DPI is significantly affected by the selection of formulation components and the processing of the formulation and, therefore, it is crucial to evaluate these parameters. This review will discuss different factors influencing the aerosol performance of carrier-based DPIs, including formulation components, device considerations, and manufacturing parameters. Additionally, novel technologies pertaining to the optimization of DPI performance are also discussed.